INVENTORY OF WEST JAVA BLACK LANGUR [Trachypithecus mauritius] FEEDING PLANTS IN THE BOGOR TAMAN SAFARI INDONESIAN FOREST AREA - Manansang, Jansen; Sinaga, Walberto; Mansjoer, Sri Supraptini (Jurnal Biosilampari : Jurnal Biologi, 2023)
The West Java black langur is one of the endemic primates on the island of West Java. Currently, the conservation status of the West Java black langur (Trachypithecus mauritius) is categorized as Vulnerable status, registered in Appendix II. This research was carried out from January to March 2022. The purpose of the study was to determine the types of forage plants, and the parts eaten by the West Java black langur responsive found in the Taman Safari Indonesia (TSI) Bogor forest area. The research method used is the observation method through direct observation in the field. The results showed that there were 14 types of feed for the answering West Java black langur, divided into 12 families. The most dominant parts of the plant eaten by responsive West Java black langurs are young leaves 42%, shoots 30%, and others 28%.